Amelioration of seed yield, oil content and oil quality through induced mutagenesis in sesame (Sesamum indicum L.) (Bangladesh Journal of Botany, 2015)
Thirty mutant lines selected from 3 widely adapted genotypes of sesame viz. Rama, SI 1666 and IC 21706 (ten from each of the three genotypes), developed by induced physical (?-rays) and chemical (EMS) mutagens, were evaluated against their respective control genotype for yield and its important attributes in M4 generation to reveal the ramification of mutagens for disclosing the magnitude of variation among mutants in advance generation and also to identify the promising positive mutants to refurbish new improved varieties of sesame. Mutants professing higher seed yield were evaluated for oil quantity and quality. All selected mutant lines evinced improved seed yield over their respective controls. Irrespective of the genotypes highest yield was recorded in the line induced by 0.5% EMS. Based on mean seed yield and its components, selected 10 superior mutants, also possessed high oil percentage with a better oil profile having relatively more polyunsaturated fatty acid content, specially linoleic acid, than the control, indicating potentiality of mutation breeding to restructure plants with high yield, improved oil percentage and quality. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22718 Bangladesh J. Bot. 44(1): 15-22, 2015 (March)